Thickness dependence of dielectric properties in sub-nanometric Al2O3/ZnO laminates. (December 2021) - Upadhyay, M.; Ben Elbahri, M.; Mezhoud, M.; Coq Germanicus, R.; Lüders, U.
Highlights: Al2 O3 /ZnO laminates with sub-nanometric individual layer thickness were prepared. A dielectric constant of 200 is achieved, exploiting the Maxwell-Wagner effect. The properties can be tuned by the individual layer thickness and interfacial layers. Abstract: In recent years, laminates consisting of alternating layers of two binary oxides with layer thicknesses below 1 nm have attracted attention for their high dielectric constant values, reaching values of about 1000 in the case of Al2 O3 /TiO2 sub-nanometric laminates. This excellent dielectric performance of the sub-nanometric laminates relies on the Maxwell Wagner (MW) relaxation, exploiting the blocking of the mobile charge carriers of the semiconducting TiO2 at the interface with Al2 O3 . In this work, we explore the possibilities of enhancing the dielectric constant by MW relaxation in amorphous sub-nanometric laminates of Al2 O3 /ZnO. We demonstrate that the sublayer thickness and the interface of individual layers define the apparent dielectric constant of the laminates. In addition or further understanding, simulations and equivalent circuit analysis of the sub-nanometric laminates were conducted.